Pengaruh Pengawasan Dan Pengendalian Terhadap Peningkatan Motivasi Kerja Pegawai Di Kantor Kecamatan Serang Kota Serang - dyah maharani (eCo-Buss, 2018)
Serang Subdistrict, Serang City is a sub-district located in the capital city of Banten Province, in improving the performance of the organization trying to carry out supervision and control both internally by the leadership of the organization and externally by the Agency or Inspectorate, so that the implementation of fraud, errors and omissions can be prevented. Then with supervision and control, any solution or mistake can be found a solution by providing guidance and guidance so that employees are expected to minimize errors in carrying out work, and this will motivate employees to carry out tasks in accordance with applicable regulations. As explained in the previous chapter, the number of respondents in this study was 40 people. The number of questionnaires was 40 copies consisting of 8 questions (variable X) and 11 questions involving the dependent variable (variable Y). After the questionnaire was distributed, then the recall was carried out and all questionnaires were collected. Interrelation Correlation Coefficient of Control and Control Implementation with Increased Employee Work Motivation obtained the value of correlation (r) of 0.996 While t count is 70.8> t table of 1.669, this means there is a positive and significant relationship between Implementation of Supervision and Control of Increased Work Motivation Employees at Serang District Office, Serang City. While the coefficient of determination obtained by 99.2% indicates that the Implementation of Supervision and Control as one of the factors that influence the Increase in Employee Work Motivation by 99.2%. While the rest, which is 0.8%, means that there are other factors that influence the increase in motivation for employee work